Sosialisasi Pemanfaatan Aplikasi Marketplace untuk meningkatkan pemasaran produk UMKM di Desa Meri Kabupaten Purbalingga - Sitanini, Ayu; Alfianika, Destin; Nasiroh, Siti; Renovriska, Melia Dwi; Maulita, Ika (Indonesian Journal of Community Service and Innovation (IJCOSIN), 2025)
A strategic step to improve the marketing of small and medium enterprise (MSME) products in Meri Village, Purbalingga Regency is to integrate marketplace applications. The development of digital technology has given small business owners new opportunities to grow their business through online platforms such as Shopee, Tokopedia, and TikTok Shop. The objective of this community service program is to provide MSME participants with knowledge about the advantages, working methods, and marketing tactics in the marketplace. Activities are conducted through lectures, tutorials, discussions, and hands-on guidance in creating accounts and managing online stores. The results show that participants better understand digital marketing, are more interested in adopting marketplaces, and are better able to reach a wider range of consumers. It is hoped that MSMEs in Meri Village can increase competitiveness, profits, and the welfare of local communities with continued support.